From Stall to Safe Meal: A Study on Food Safety Practices in the University Belt in Tamag, Vigan City - Chanille Fritz A. Miguel , Krizel Joy G. Ayon-Ayon, Kate Gwyneth A. Cabuan, Christine R. Navarro, Jefferson P. Natividad, Mark Angelo C. Perez, Giselle Q. Revibes, Cherry B. Banilad (South Eastern European Journal of Public Health, 2024)
Introduction: Food safety is a shared responsibility in food service, with convenience and affordability attracting low-income workers. Contamination remains a concern, necessitating hygiene and sanitation for all handlers. Objectives: This study aimed to determine the food safety practices of food servers and servers along the university belt in Brgy. Tamag, Vigan City, Ilocos Sur. Methods: This study employed a descriptive-correlational design to examine the relationship between socio-demographic factors and food safety practices among food stall servers, using a questionnaire adapted from Asmawi et al. (2018). Ethical approval and consent ensured participants' rights, and data were analyzed using frequency counts, percentages, means, and Pearson correlation Results: The food handlers have a good adherence to food safety, with a very good practice along food storage and serving, though only good in personal hygiene, food preparation, and waste management. Significant relationships were found between age and waste management, and an inverse relationship between educational attainment and food storage practices. Conclusions: The food stall servers exhibit excellent food safety practices, with age and education influencing specific practices, emphasizing the need for targeted interventions.